Egg yolk hydrolysate shows osteogenic activity in MC3T3-E1 osteoblastic cells - Ilekuttige Priyan Shanura Fernando; Pauline Duffuler; Jianping Wu (Journal of Functional Foods)
There is growing interest in natural bioactive compounds for bone health, with egg yolk peptides showing promise owing to their osteogenic properties. However, previously reported extraction and purification methods are costly and time-consuming. This study explored the osteogenic properties of water-soluble egg yolk peptide fractions obtained using methods that are easily scalable for industrial production. Three different fractions were prepared: FA, water-soluble egg yolk fraction; FB, salt-soluble egg yolk fraction; FC, salt-soluble hydrolyzed egg yolk fraction. Effects of fractions were evaluated on osteoblastogenesis. FC, obtained via Protease M and Lipase AY digestion, stood out compared to FA and FB, demonstrating improved MC3T3-El proliferation, RUNX2 production, Akt phosphorylation, and osteoid mineralization. FC contains phosvitin and vitellogenin. The <3 kDa subfraction of FC obtained by ultrafiltration indicated a higher osteogenic potential in MC3T3-E1 preosteoblasts. These findings indicate that the egg yolk hydrolysate obtained by the FC method could be a promising source for formulating functional foods that enhance bone health.